Identifying malicious activities through anomaly detection in ethereum network - Neo, Remus Keng Long (Nanyang Technological University, 2023)
The growth in blockchain technology has also brought about the rise in number of decentralized applications (dApps). dApps are open-sourced applications that operates on a blockchain network and has numerous benefits over conventional applications that we know. A key feature of dApps is the smart contract that powers it. Users interact with smart contracts through transactions to perform functions on dApps. With the growth in popularity of dApps, the occurrences of cyber-attacks have also noticeably increased. Hence, there is a need to ensure security and data on dApps are not easily breached. This project aims to develop a method to identify malicious transactions in smart contracts through the use of block explorers to consolidate historical transactional data, together with data analysis.